SENDERIZACIÓN Y SEÑALÉTICA PARA EL PARQUE RECREACIONAL YAMBURARA DE LA PARROQUIA VILCABAMBA, CANTÓN Y PROVINCIA DE LOJA - Mejía Encalada, Katherine Abigaíl (2016)
Ecuador is a privileged country that arouses curiosity and interest in those wanting to experience a deep contact with nature, is also a multiethnic and multicultural nation. South of Ecuador, in the Sierra Region is located in the Province of Loja, in the canton of the same name 45 km from the provincial capital Loja is the rural parish Vilcabamba called The Sacred Valley, because of its geographical location and exceptional conditions climatic, natural and cultural, is recognized as Island Immunity for World heart disease and Longevity Center, a natural paradise, earth life, where death is slow to get the men. Throughout the area has natural attractions and cultural potential to develop tourism programs and resources projects. This project entitled "TRAILING AND SIGNAGE FOR RECREATIONAL PARK Yamburara VILCABAMBA PARISH, CANTON AND PROVINCE OF LOJA" was held with the firm intention to revive, stimulate and support the tourism sector progress based primarily on the Corporate Manual Signaling Tourism Ministry of Tourism, a document that served as a technical guide for the preparation of this research work. For the preparation of this project was considered as an area of study Yamburara Recreational Park located in the Vilcabamba parish, this parish is located in the south-eastern part of the province of Loja. In order to develop the theme three specific objectives: 1. Conduct an analysis of the current tourism situation Yamburara Recreational Park. 2. Propose senderización and signage of Yamburara Recreational Park. 3. Socialize proposal senderización and signage of Yamburara Recreational Park to the community. To give compliance to each of the objectives was necessary to apply appropriate methods and techniques as well, for the first specific objective the analytical method it allowed an analysis to the current situation of the park was used also resorted to the matrix of the author Carla Ricaurte for the relevant diagnosis. It was taken as main sources practices, theses, research papers and other studies that rest in the municipal GAD Canton Loja combined with the technique of direct observation and using the tab attractions proposed by the MINTUR, could prioritize the Recreational Park Yamburara. To meet the second objective concerning the trailing the technical specifications of the trail by reference standards MINTUR determined, moreover analysis of capacity was conducted using the methodology of the author Miguel Cifuentes with which it was established maximum number of views that can receive path. For the signage was taken as the base document for Tourism Signage Corporate Manual for the design and location of the corresponding signage. 5 A form where a description of the appropriate signage where informative data consist signal type, function, location, the corresponding graphic design, legend, materials, type of maintenance, cost and time of execution was performed. So too it has the development of a referential budget considering all the features of the signage and implementation costs within the park. To give compliance to the third objective Method rapid analysis and participatory planning (MARPP) was applied whose application served to the socialization process of this project both in the community of Vilcabamba and Loja, allowing people to interact with the sites mentioned above and take into account the views expressed by them to subsequently generate alternative proposals addressed to enhance this appeal. He developed the objectives and the research phase was concluded that the research area has great tourism potential but currently has deficiencies which make necessary the intervention of the competent authority, but nevertheless, the path by virtue of their length, outstanding comfort and is suitable for every kind of visitor who walk the same. Taking into account the results obtained, also it concludes that this proposal is seen as a viable alternative is thus contribute to the development of recreational park Yamburara that your current infrastructure is designed to be visited by 366 people a day. To give effect to the path a signaling system was designed along the lines proposed by the INEN Standards, in the Corporate Manual tourist signs. The signals proposals are informative ballots, information panels, directional signage and directional information signs at strategic points of the path and landfills. Recommendations arising at the end of this paper are mainly directed to the Autonomous Government Decentralized Municipal de Loja and administration Yamburara Recreational Park, which are the bodies responsible for promoting activities for the benefit and development of the Park, to consider in its planning this research project in the future can implement the proposed trailing and signage described here.